Higher education for citizens of caring democracies - Tronto, J.C. (South African Journal of Higher Education, 2018)
Educational development has gained legitimacy as a field of inquiry. Larger structural questions about the place of universities within democracies, however, should be a basic concern of educational developers. This paper poses the question, “which side are you on?” It argues that developers can either acquiesce to the conditions of universities in a neoliberal setting or can resist by thinking about universities as a critical tool in the development of caring democracies.